2010
DOI: 10.4038/sljch.v39i2.1957
|View full text |Cite
|
Sign up to set email alerts
|

An observational study on retinopathy of prematurity in the neonatal intensive care unit at Teaching Hospital, Peradeniya, Sri Lanka

Abstract: Objectives: This was a clinical audit, conduct to know the rational practice of anti-d prophylaxis in two early pregnancy complications. Methods: Information was gathered from 37 patients with early trimester miscarriages and 35 patients with ectopic pregnancies who admitted to Professorial gynecology ward, Teaching hospital, Peradeniya over single calendar year period. Data gathered from retrospectively from bed head tickets and recorded/ analysed with SPSS V21. Results: Among patients who had early trimester… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…A study done in the Teaching Hospital Peradeniya (THP) over a 16 month period from February 2003 to determine the incidence of ROP in the Neonatal Intensive Care Unit of THP revealed that 15 out of 106 screened neonates had significant ROP (i.e. stage 3 and beyond) 5 .…”
Section: Discussionmentioning
confidence: 99%
“…A study done in the Teaching Hospital Peradeniya (THP) over a 16 month period from February 2003 to determine the incidence of ROP in the Neonatal Intensive Care Unit of THP revealed that 15 out of 106 screened neonates had significant ROP (i.e. stage 3 and beyond) 5 .…”
Section: Discussionmentioning
confidence: 99%